THE CONCEPT OF CHILD IN THE PERSPECTIVE OF THE QUR’AN (THEMATIC INTERPRETATION STUDY) - Abd Halim Nasution (JURNAL TARBIYAH, 2020)
The revival of Islamic religion has formed a new atmosphere for the condition or fate of the children of Arabs. Islam forbids the killing of children through the prohibition of Allah, among others, contained in QS. Al-Isra/17: 31. Besides prohibits killing children, featuring the provisions of Islamic law that shows how important attention to and even how to look after children with a loving since before and after birth. The Qur’anic view of children globally formulated in the principle:"The children do not cause problems and suffering of parents and also vice versa" In the Qur’an, Allah says "Do not be a mother suffering difficulties because of his son and father do not have to suffer because of his son, and likewise heir duty.” Qur'an has serious concern about the child. This is evident from the various terms used in the Qur’an to show the meaning of the child as źurriyah, ibn, walad, sabiy, usbah, gulam, thifl, nasl, rabaib, and ad'iya '. As a review of the limitation, this study will analyze the concept of child in the perspective of the Qur'an (interpretation of thematic studies).